The Analysis of Stress Distribution on the Physical Model of Road Base Layer - Ganjur Giwangkara, Grawira; Mohamed, Azman; Md. Nor, Hasanan; A. Khalid, Nur Hafizah (International Journal of Integrated Engineering, 2020)
The road base layer as a primary foundation for the flexible pavement needs to provide adequate strength for the working load. The road base layer which is constructed from a gradation of aggregate must distribute the stress as wide as possible to reduce the load per square area. The action of stress distribution on the road base layer mostly relies on its grain-to-grain interaction. This research used the natural crushed aggregate (NCA) and the recycled concrete aggregate (RCA) as the road base materials. Physical models were conducted to evaluate the stress distribution under a static load. The physical model was using a box with a dimension of 620 mm x 620 mm x 500 mm. There were three layers for the physical model such as the road base layer, sub-base layer, and subgrade layer. The thickness of each layer was 200 mm, 100 mm, and 200 mm respectively. A static load with a maximum of 20 kN in the increment of 1 kN was added. The result of the scaled-model was not as similar to the theory of Boussinesq related to the stress distribution. The characteristic of the materials will show a different behavior of the stress distribution.